Influence Risk Awareness And Development Source Power Humanity Against Employee Performance At Banking In Balikpapan - Tiara Erika Amalia; Muliyadi Hamid; Nurmadhani Fitri Suyuthi (International Journal of Economics and Management Research, 2024)
Study This aims To know And analyze The influence of Risk Awareness on Employee Performance in Banking in Balikpapan And analyze the influence of Development Source Power Man on the Performance of Employees in Banking in Balikpapan. The method study used is method quantitative. The number of respondents was 84 people. Analyze data using analysis regression linear multiple with the use of Soft Ware SPSS. Results study show Risk Awareness is influential in a way significant to the Performance Employee of banking in Balikpapan, matter This concluded from the data obtained with a significance value of 0.000 < 0.05. The results of this research, prove that Risk Awareness Which Good capable increase Performance in Employee, Development HR has a significant effect on Employee Performance in banking in Balikpapan, this is concluded from the data obtained with the value results significance as big as 0,000 < 0.05. From results show that the Development of HR Which is Good increases the Performance of employees together, the variable Risk Awareness And the Development of HR are influential and significant to the Performance of Employees. The more good Risk Awareness And Development HR given to Employee Performance in Banking in Balikpapan will increase.